Answer:
y = -24 + -2x + 2x2
Step-by-step explanation:
Simplifying:
y = 2(x + 3)(x + -4)
reorder the terms:
y = 2(3 + x)(x + -4)
multiply (3 + x) * (-4 + x)
y = 2(3(-4 + x) + x(-4 + x))
y = 2((-4 * 3 + x * 3) + x(-4 + x))
y = 2((-12 + 3x) + x(-4 + x))
y = 2(-12 + 3x + (-4 * x + x * x))
y = 2(-12 + 3x + (-4x + x2))
Combine like terms 3x + -4x = -1x
y = 2(-12 + -1x + x2)
y = (-12 * 2 + -1x * 2 + x2 * 2)
y = (-24 + -2x + 2x2)
Solving:
y = -24 + -2x + 2x2
solving for variable 'y'
Move all terms containing y to the left, all other terms to the right.
Simplifying:
y = -24 + -2x + 2x2
Arcs are just sections of the circle
so lets say you had a pizza
and you put some points on the crust, the legnth of the crust from point to point is that arc
example
if you put poins A and B, then arc AB is the crust between points A and B
arcs can include other points as well
and arc AB=arc BA
so
I wil name easy arcs first
arc AB
arc BC
arc CD
ard DA
now ones that include others
arc AC
arc BD
so the arcs you might want to list are
arc AB
arc BC
arc CD
ard DA
arc AC
arc DB
Answer:
It is not a function because the output of 9 repeats.
(1,9) (4,9)
:D
Answer:
6x-5y=4
6x+3y=30
Step-by-step explanation:
Move variable to the left
5y=6x-4
Reorder the terms
5y-6x=-4
Change the signs
-6x+5y=-4
Move variable to the left
3y=-6x+20
Reorder the terms
3y+6x=20